Data-driven PID control for DC/DC buck-boost converter-inverter-DC motor based on safe experimentation dynamics - Mohd Riduwan, Ghazali; Mohd Ashraf, Ahmad; Raja Mohd Taufika, Raja Ismail (Universiti Malaysia Pahang, 2019)
This research paper presents a data-driven PID control for a DC/DC Buck-Boost converter-inverter-DC motor system based on safe experimentation dynamics (SED). The data-driven is a control scheme refers to a controller that is designed using the input-output data measurement obtained from an actual plant. Then, the data-driven scheme required an optimization tool for finding the optimal parameter controller design with the help of the running data. Hence, the SED is an optimization method provides high accuracy solution by keeping the best controller parameter values based on the input-output data measurement. Moreover, the SED method is a single agent-based optimization that provides a fast solution in order to find an optimal solution, especially in the high dimensional problem. Apart from that, a proportional-integral-derivative (PID) controller structure is chosen due to its simple structure and robust performance that allows it to be used for a wide range of operating conditions. The performance of the data-driven PID control based on the SED method is evaluated by an extensive numerical example based on the tracking performance and computational time for DC/DC buck-boost inverter-converter of DC motor. In addition, the performance accuracy of the SED based method is compared to simultaneous perturbation stochastic approximation (SPSA) based method. The simulation results show that the data-driven PID based on the SED is capable to track the trajectory task given and obtain a better control accuracy as compared to the SPSA based method.